MATERNAL MENTAL HEALTH: STUDY OF COPING STRATEGIES MOTHERS WITH EXPERIENCING POSTPARTUM BLUES - Kurniasari Pratiwi; Endang Khoirunnisa (Universitas Karya Husada Semarang, 2024)
Postpartum blues is an uncomfortable feeling experienced by mothers after giving birth. The incidence of postpartum blues in Indonesia is quite high, between 50-70%. This research aims to explore coping strategies for postpartum blues sufferers using qualitative research methods with case studies. Two participants who experienced postpartum blues were selected by purposive sampling technique. Method Data collection was carried out through in-depth interviews. Researchers used open questions with a grid of questions about coping strategies for dealing with postpartum blues and The Edinburgh Postnatal Depression Scale (EPDS). Data verification process was carried out by triangulating data and sources (husbands and people closest). Research results known that the strategy used by respondents to overcome postpartum blues is Emotional Focused Coping. Other things can do to overcome postpartum blues include doing fun activities (me time), a spiritual approach, telling stories and being sincere. Based on evidence, it is known that distress due to breastfeeding problems (nipple pain) can cause postpartum blues syndrome. The new thing found in this research is that having sexual relations with husband can be a way to overcome postpartum blues. A good social support system needs to be built by all parties to support maternal mental health